Prospects for γ-ray observations of narrow-line Seyfert 1 galaxies with the Cherenkov Telescope Array – II. γ–γ absorption in the broad-line region radiation fields. Issue 1 (3rd March 2020) - Romano, P; Böttcher, M; Foschini, L; Boisson, C; Vercellone, S; Landoni, M
ABSTRACT: Gamma-ray emitting narrow-line Seyfert 1 (γ-NLS1) galaxies possibly harbour relatively low-mass black holes (10 6 –10 8  M⊙ ) accreting close to the Eddington limit, and share many characteristics with their sibling sources, flat-spectrum radio quasars. Although they have been detected in the MeV–GeV band with Fermi –LAT, they have never been seen in the very high energy band with current imaging atmospheric Cherenkov telescopes (IACTs). Thus, they are key targets for the next-generation IACT, the Cherenkov Telescope Array (CTA). In a previous work we selected, by means of extensive simulations, the best candidates for a prospective CTA detection (SBS 0846+513, PMN J0948+0022, and PKS 1502+036) taking into account the effects of both the intrinsic absorption (approximated with a cut-off at 30 GeV), and the extragalactic background light on the propagation of γ-rays. In this work, we simulate the spectra of these three sources by adopting more realistic broad-line region (BLR) absorption models. In particular, we consider the detailed treatment of γ–γ absorption in the radiation fields of the BLR as a function of the location of the γ-ray emission region with parameters inferred from observational constraints. We find that, due to the energy range extent and its sensitivity, CTA is particularly well suited to locate the γ-ray emitting region in γ-NLS1. In particular CTA will be able not only to distinguish whether the γ-ray emitting region is located inside or outside the BLR, but also where inside the BLR it may be.